Environmental Education And Mirota Beach Clean-Up Actions To Realize Sustainable Marine Tourism In Batam City - Mulyadi, Tirta; Frangky Silitonga; Hari Sandi Atmaja; Wahyudi Ilham; Febriyanti Dwi Cahyani (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
This study investigates the implementation of the Environmental Education and Mirota Beach Clean-Up Action as a community-based initiative to support sustainable marine tourism in Batam City, Indonesia. Mirota Beach, one of Batam’s prominent coastal destinations, has been facing increasing environmental pressures due to rising tourist activity, improper waste disposal, and limited awareness of coastal conservation. Using a qualitative case study approach, data were collected through observations, interviews, and documentation involving students, local residents, tourism operators, and destination managers. The program integrated environmental education, waste management training, and collaborative clean-up activities conducted with more than 30 participants. The results demonstrate significant improvements in environmental awareness, with over 80% of participants showing increased understanding of the 3R (Reduce, Reuse, Recycle) principles and sustainable marine tourism practices. The clean-up action directly contributed to enhancing the beach’s cleanliness while fostering community engagement and developing a sense of ownership toward environmental preservation. The initiative also produced academic benefits for participating students through experiential learning aligned with higher education’s Tri Dharma. Furthermore, the formation of the Mirota Beach Care Community and ongoing partnerships with local stakeholders highlight strong potential for long-term sustainability. Overall, this program serves as a practical model of collaborative environmental stewardship that supports the achievement of SDG 11 (Sustainable Cities and Communities) and SDG 14 (Life Below Water), and it offers replicable strategies for other coastal destinations in Indonesia.